Pengenalan Makanan 4 Sehat 5 Sempurna dengan Media Playdough pada Anak Usia 5-6 Tahun di TK Islam Plus Qamarul-Lail Aikmel - Siti Yaumul Afifah Afifah; Muazzar Habibi; Ika Rachmayani; Baik Nilawati Astini (Indonesian Journal of Elementary and Childhood Education, 2021)
Based on the research result and discussion about introduction 4 healthy 5 perfect food using playdough to children aged 5-6 at Islam Plus Qamarul-Lail kindergarten, it can be concluded that the food was introduced using pictures to show the children the image of 4 healthy 5 perfect food, the name of each food was written in the children’s workbook to strengthen their memory and knowledge about the food. The researcher also introduced the materials to make the playdough and explained the steps of making it which would be used to make the replica of food. The result showed that the children were familiar with the name of 4 healthy 5 perfect foods thus showing the score of each descriptor as shown in the table i.e. indicator 1 is 75%, indicator 2 is 70%, and indicator 3 is 71%. Each indicator sets the descriptors that each child should achieve. One of the descriptors depicted that some children encountered a little problem to replicate a glass that contained milk because the process was too complicated for the children. However, each child achieved the most descriptors. The result showed that most children got 3 scores which means the children were familiar with most items in 4 healthy 5 perfect food after they were introduced to the food using pictures at the first stage.